Exploring shadow puppetry as alternative instructional medium - Vela, Jualim Datiles (2006)
This study explored the effectiveness of shadow puppetry as an instructional medium for alternative and interactive learning experience for students in public elementary schools. The study underwent research, development, production, and implementation of instructional materials in environmental science utilizing shadow puppetry. A shadow puppetry focused was developed using ASSURE. To test its effectiveness, the researcher taught a lesson in environmental science using puppetry to Grade 3 students of Bay Central Elementary School and was consequently evaluated for revision and adjustment. Results have shown that shadow puppetry provides an effective alternative learning experience to students. They find the lesson more interesting and engaging with the puppets, therefore making learning more effective and teaching more efficient.